Optimizing Discharge Processes to Alleviate Emergency Department Overcrowding: An Audit in a Central Malaysian Tertiary Hospital - Thaalitha Naidu; Nurulalnissa Abdul Kadir; Suriya Kumareswaran Vallasamy (Fakultas Kesehatan Masyarakat, Universitas Muhammadiyah Palu, 2025)
Introduction: Emergency Department (ED) overcrowding is a global challenge, often exacerbated by delays in discharging patients from inpatient wards. In Malaysia, this issue is especially pressing in tertiary hospitals, where prolonged discharge times hinder bed turnover and contribute to ED congestion. Methods: A 30-day cross-sectional audit was conducted in a medical ward of a central tertiary hospital in Malaysia, involving 109 consecutively discharged patients selected via total sampling. Discharge duration was measured from the point of medical fitness for discharge to actual bed vacancy. Data were analysed using descriptive statistics to identify patterns and sources of delay. Results: The mean discharge duration was 420 minutes—more than double the 180-minute target—with only 7% of patients meeting the benchmark. Key delay factors included insufficient pre-discharge planning, limited staffing, delayed documentation and pharmacy processes, poor IT infrastructure, logistical challenges, and social support issues. Complex cases requiring multidisciplinary input experienced the longest delays. Conclusion: To improve hospital efficiency and reduce ED overcrowding, hospitals should implement structured early discharge planning, enhance staffing, upgrade digital infrastructure, and establish a discharge lounge. Strengthening interdepartmental coordination and integrating social support services earlier in the discharge process are also crucial.